Control behaviors and thermal comfort in a shared room with desk fans and adjustable thermostat - He, Yingdong; Li, Nianping; Li, Na; Li, Jia; Yan, Jinbo; Tan, Chang (Building and environment, 2018)
It is well known that fans help maintain thermal comfort in warm environments. Nonetheless, two important questions are unclear: (1) how occupants use fans and control the air conditioner thermostat simultaneously, and (2) how behaviors of occupants interact in a shared room with personal fans. In this study, a series of experiments was conducted with subjects placed in environments having desk fans, with and without the access to controlling indoor temperature. The results show that desk fans significantly reduced warm sensation and improved thermal comfort in the conditions at 28 and 30 °C, while subjects still needed to adjust the indoor temperature until they fully eliminated the warm sensation. Moreover, subjects tended to use desk fans less when they could adjust the indoor temperature. Notably, it was found that insensitive subjects always made concessions to sensitive subjects, and thus the indoor environment was always controlled by sensitive subjects. Moreover, the always-on strategy of desk fans made both sensitive and insensitive subjects choose the higher temperature, and also maintained the same level of thermal comfort as compared with other conditions. This strategy can be regarded as a trade-off between thermal comfort and energy conservation. •Subjects with fans still adjusted indoor temperature till all of them felt neutral.•Subjects used fans less as they could adjust indoor temperature simultaneously.•The concession effect was observed in the co-control behaviors over thermostat.•The always-on strategy of fans balanced thermal comfort and energy conservation.